2006
DOI: 10.1128/jvi.80.6.3112-3115.2006
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirement for Conserved Tryptophans in Human Immunodeficiency Virus Type 1 Vif for the Selective Suppression of APOBEC3G and APOBEC3F

Abstract: APOBEC3G (A3G) and related cytidine deaminases, such as APOBEC3F (A3F), are potent inhibitors of retroviruses. Formation of infectious human immunodeficiency virus type 1 (HIV-1) requires suppression of multiple cytidine deaminases by Vif. Whether HIV-1 Vif recognizes various APOBEC3 proteins through a common mechanism is unclear. The domains in Vif that mediate APOBEC3 recognitions are also poorly defined. The N-terminal region of HIV-1 Vif is unusually rich in Trp residues, which are highly conserved. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
101
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 47 publications
(48 reference statements)
8
101
1
1
Order By: Relevance
“…Most of our understanding about APOBEC3 activity and corresponding Vif defects has been gained by using overexpression systems (18,19,25). In this study, we demonstrate that HIV-1 Vif mutants with suboptimal anti-APOBEC3G activity display reduced fitness in a multiple round replication assay with human PBMCs.…”
Section: Table 1 Summary Of Hiv-1 Drug Resistance Mutations That Resmentioning
confidence: 79%
See 1 more Smart Citation
“…Most of our understanding about APOBEC3 activity and corresponding Vif defects has been gained by using overexpression systems (18,19,25). In this study, we demonstrate that HIV-1 Vif mutants with suboptimal anti-APOBEC3G activity display reduced fitness in a multiple round replication assay with human PBMCs.…”
Section: Table 1 Summary Of Hiv-1 Drug Resistance Mutations That Resmentioning
confidence: 79%
“…Protection of HIV-1 from cytidine deamination in vivo, however, is not absolute, because full-length Vif alleles that fail to neutralize one or several APOBEC3 enzymes have been identified (18,19). Indeed, HIV-1 sequences carrying the genetic footprints of past deamination have been detected in treated and untreated chronically infected patients (20)(21)(22), vertically infected infants (23), and long-term nonprogressors (18,24) suggesting that variations in HIV-1 Vif's anti-APOBEC3 activity occur in many different clinical settings.…”
mentioning
confidence: 99%
“…In addition, we identified a region important for A3H-hapII neutralization that is not required for A3F or A3G neutralization. Studies conducted by us and others have determined that Vif1 also has distinct regions for the neutralization of A3F, A3G, and A3H-hapII (34)(35)(36)(37)(38)(39). It is important to point out that it cannot be concluded that these motifs that have been identified to be critical for interaction through mutational analyses are themselves directly involved in the protein-protein interactions.…”
Section: Discussionmentioning
confidence: 94%
“…Vif1 interacts with numerous host cell proteins to form a ubiquitin ligase complex consisting of cullin 5, elongin B, and elongin C (29), RING finger protein 2 (30,31), and CBF␤ (32,33). Further, Vif1 has several domains through which it binds APOBEC3 proteins, with some regions being specific for certain APOBEC3s (34)(35)(36)(37)(38)(39). For example, the 40 YRHHY 44 motif of Vif1 is known to play a critical role in inducing the degradation of A3G, while the 14 DRMR 17 region is known to be critical for inducing the degradation of A3C, A3D, and A3F (34).…”
mentioning
confidence: 99%
“…These shared features of A3G and A3F seemingly accord with the view that these are the most significant APOBEC enzymes in terms of natural HIV-1 infection (namely in humans). Interestingly, the sequence elements within HIV-1 Vif required for inhibition of A3G versus A3F differ from each other (Simon et al 2005;Tian et al 2006;Russell & Pathak 2007), implying that evolutionary pressures have selected for the ability to suppress both proteins. Moreover, A3G and A3F are both expressed in human CD4 T cells (the principal target for HIV-1 infection in vivo), further supporting the notion that both enzymes naturally encounter HIV-1, and that the virus must have evolved to evade the anti-viral activities of each of them.…”
Section: Anti-hiv-1 Phenotypes Of Diverse Human Apobec Proteinsmentioning
confidence: 99%